Gating Effects for Ion Transport in Three‐Dimensional Functionalized Covalent Organic Frameworks. (9th February 2022) - Yu, Xiuqin; Li, Cuiyan; Chang, Jianhong; Wang, Yujie; Xia, Weifeng; Suo, Jinquan; Guan, Xinyu; Valtchev, Valentin; Yan, Yushan; Qiu, Shilun; Fang, Qianrong
Abstract: The development of bioinspired nano/subnano‐sized (<2 nm) ion channels is still considered a great challenge due to the difficulty in precisely controlling pore's internal structure and chemistry. Herein, for the first time, we report that three‐dimensional functionalized covalent organic frameworks (COFs) can act as an effective nanofluidic platform for intelligent modulation of the ion transport. By strategic attachment of 12‐crown‐4 groups to the monomers as ion‐driver door locks, we demonstrate that gating effects of functionalized COFs can be activated by lithium ions. The obtained materials exhibit an outstanding selective ion transmission performance with a high gating ratio (up to 23.6 for JUC‐590), which is among the highest values in metal ion‐activated solid‐state nanochannels reported so far. Furthermore, JUC‐590 offers high tunability, selectivity, and recyclability of ion transport proved by the experimental and simulated studies. Abstract : Crown ether‐functionalized 3D COFs can efficiently gate ion transport with an excellent gating ratio up to 23.6 are reported, which is among the highest values in metal ion‐activated solid‐state nanochannels reported so far.